2023
DOI: 10.17504/protocols.io.j8nlk4zpxg5r/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acclimation of in vitro grown individual lines of big sagebrush (Artemisia tridentata) to ex vitro conditions in support of genotype-by-environment experiments and restoration v2

Abstract: The following protocol describes the ex vitro, hardening and acclimation of in vitro grown genetically identical plantlets (i.e. clones) of Artemisia tridentata ssp. tridentata (Asteraceae). The goal of this protocol is to create functional clonal lines of Artemisia tridentata to be used in genotype-by-environment (GxE) experiments. Overall, the protocol consists of the following four major steps and takes 16 weeks to complete on 11-16-week old in vitro plantlets: i) transfer in vitro plantlets from modified M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Ψ soil was used to guide the watering regime (using TEROS‐21 probes; METER Group, Pullman, Washington, USA) during in vitro to ex vitro acclimation and hardening to reduce mortality at this critical step of our protocol. Ψ soil should be maintained above −0.1 MPa for well‐watered conditions and between −0.2 and −0.9 MPa for hardening purposes (Drivas and Everett, 1988; see Figure 8 in Martinez et al, 2022). In addition, we found that when the plantlets in silty soil (see below for more details) were exposed to soil water potentials of −1 MPa (see Figure 8 in Martinez et al, 2022), the Ψ shoot declined to about −2.2 MPa, which based on preliminary work in our lab, could lead to stomatal closure in sagebrush seedlings and mortality by hydraulic failure.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ψ soil was used to guide the watering regime (using TEROS‐21 probes; METER Group, Pullman, Washington, USA) during in vitro to ex vitro acclimation and hardening to reduce mortality at this critical step of our protocol. Ψ soil should be maintained above −0.1 MPa for well‐watered conditions and between −0.2 and −0.9 MPa for hardening purposes (Drivas and Everett, 1988; see Figure 8 in Martinez et al, 2022). In addition, we found that when the plantlets in silty soil (see below for more details) were exposed to soil water potentials of −1 MPa (see Figure 8 in Martinez et al, 2022), the Ψ shoot declined to about −2.2 MPa, which based on preliminary work in our lab, could lead to stomatal closure in sagebrush seedlings and mortality by hydraulic failure.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Ψ soil should be maintained above −0.1 MPa for well‐watered conditions and between −0.2 and −0.9 MPa for hardening purposes (Drivas and Everett, 1988; see Figure 8 in Martinez et al, 2022). In addition, we found that when the plantlets in silty soil (see below for more details) were exposed to soil water potentials of −1 MPa (see Figure 8 in Martinez et al, 2022), the Ψ shoot declined to about −2.2 MPa, which based on preliminary work in our lab, could lead to stomatal closure in sagebrush seedlings and mortality by hydraulic failure. Thus, the watering regime recommended in our protocol is more conducive to optimal growth in preparation for G×E experiments.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations